EVALUASI SIFAT FISIKA KIMIA DAN TANGGAP RASA TABLET HISAP DEKOKTA DAUN MENGKUDU (Morinda citrifolia L.) DENGAN VARIASI PEMANIS - M. Fatchur Rochman; Mufrod Mufrod; Feyzar Habib Reynaldo; Ayuk Siti Fatimah; Yayang Rusyta Dewi (Universitas Wahid Hasyim Semarang, 2019)
ABSTRACTNoni leaf (Morinda citrofolia L.) has antioxidant compounds that can inhibit and counteract free radicals. Decocta Noni leaf to make more practice preparation of lozenges. This study aims to evaluate the physical chemical characteristics and taste response of lozenges with variations of sweeteners to cover the bitter taste of Noni leaves. Decocta mengkudu leaf is obtained by boiling at 90C for 30 minutes. Suction tablets made 9 formulas based on variations of sweeterners sucrose-water sweetener, sorbitol-sucrose-sugarcane water, and aspartame-sucrose-sugarcane water. The suction tablet is made by molding mixture method. Evaluation of physical chemical characteristics including hardness and solubility were analyzed statistically using one-way ANOVA with 95% confidence level, followed by tukey test, weight uniformity, taste response and thin layer chromatography analyzed descriptively. The results of the study was showed that influenced the increase in hardness and dissolution time and the results of the requirements physical lozenges The results of the TLC test of lozenges and decocytes showed an RF value close to Quercetin. The taste response test results showed formula I with variations of sugarcane-sucrose water sweetener, formula III with variations in sorbitol-sucrose-sugarcane-water sweetener and sugarcane water aspartame-sucrose was the most preferred by respondents of 85% - 95%.Keywords: leaf of morinda citrifolia l., lozenges, sorbitol, aspartame, sucrose, sugarcane water